Papel dos nervos renais, corpúsculos carotídeos e aldosterona na hipertensão arterial renovascular de Goldblatt - Lincevicius, Gisele Silverio [UNIFESP] (2017)
Introduction: It is already known that sympathetic nervous system (SNS), carotid body (CB) hypertonicity and renin-angiotensin-aldosterone system (RAAS) have an important role in the generation and maintenance of renovascular hypertension 2kidneys-1clip (2K1C). The main effectors of RAAS are the angiotensin II (Ang II) and aldosterone (Aldo) which acts in specifics receptors and promotes increase of blood pressure (BP) and sympathetic hyperactivity. Recently, has been shown that CB hypertonicity precedes the installation of hypertension in the 2K1C model, this can be related with the hypersensitivity to Ang II and sympathetic hyperactivity in this model. The sympathetic overdrive can be a product of afferent activation from some tissues, such as the kidneys and CB in the 2K1C model. Recent studies show that total renal denervation (DnX) reduced BP and sympathetic hyperactivation, in the same way carotid sinus denervation (CSD) produces similar effects and in addiction improves the renal function in the 2K1C animals. Hypothesis: We believe that renal nerves has an important role on the reflex and tonic control of sympathetic nerve activity to renal, lumbar and cardiac territories in the 2K1C model. The mechanism of cardiovascular and autonomic regulation are Ang II-sensitized and this sensitization could be maintained even after the reversal of hypertension though silver clip-withdrawal in the 2K1C animals. Furthermore, we believe that there is a crosstalk between the kidneys and CB, and the Aldo participates of this crosstalk mineralocorticoid receptor-via in the 2K1C model. Aims and methods: The present study evaluated the DnX effects (renal efferent and afferent signaling removal) from ischemic kidney on the tonic and reflex control of sympathetic nerve activity to renal, lumbar and cardiac territories. The effects of interaction between Ang II and Aldo chronically on the tonic and reflex control of renal SNA (rSNA) and lumbar SNA (lSNA) though previous conditioning and subsequent treatments with type 1 receptor of Ang II (AT1) and/or mineralocorticoid receptor (MR) blockade were also evaluated in the 2K1C model. Considering our hypothesis that the hipersensitivity of Ang II is maintained even after reversion of renovascular hypertension, we also evaluated the effects of withdrawal of silver clip after 4th weeks of renovascular hypertension induction. We also evaluated the effects of acute and chronic Ang II intracerebroventricular (ICV) infusion on cardiovascular, autonomic and renal systems in the 2K1C model. Furthermore, it was evaluated in this study the cross talk between the kidneys and CB through renal afferent denervation (RND) and peripheral chemoreceptor resection (CBR) as well as the role of Aldo in this cross talk in the renovascular hypertension model. Results: The increase in the sympathetic nerve activity and baroreflex dysfunction were also found to lumbar territory in 2K1C model. The DnX reduced mean arterial pressure, normalized SNA to both territories evaluated (renal and lumbar) and induced a non uniform effects on arterial baroreceptor function in the 2K1C model. We did not found significant results in the sensitization process induced by conditioning of AT1 and MR receptor antagonists. However, when we evaluated the sensitization process to endogenous RAAS by removing the silver clip, we verified that the renal system remains sensitized by Ang II, because water intake and urinary flow remained increased in the animals submitted to silver clip removal even with normalization of BP and SNA. Furthermore, we found that both RND and CBR prevented further increase in the BP and reduced rSNA (contralateral kidney), however the CBR was more effective to reduce the rSNA than RND. Additionaly, the RND and MR receptor-blockade reduced peripheral chemoreflex evoked-stimulus from cyanide in the 2R1C model. Conclusion: All together these data suggest that the renal nerve plays an important role in tonic and reflex control for different territories in the 2R1C model. The hypersensitivity to Ang II remains even after the reversal of renovascular hypertension affords to potentiate the late effects in this model. There is a crosstalk between kidneys and CB and it is mediated by MR-acting Aldo in the renovascular hypertension animal model.